Modeling with a Conceptual Representation: Is It Necessary? Does It Work? - Jordan, Rebecca C.; Gray, Steven; Sorensen, Amanda E.; Pasewark, Samantha; Sinha, Suparna; Hmelo-Silver, Cindy E. (Frontiers in ICT, 2017)
In response to recent educational imperatives in the United States, modeling and systems thinking have been identified as being critical for science learning. In this paper, we investigate models in the classroom from two important perspectives: (1) from the teacher perspective to understand how teachers perceive models and use models in the classroom and (2) from the student perspective to understand how student use model-based reasoning to represent their understanding in a classroom setting. Qualitative data collected from 19 teachers who attended a professional development workshop in the northeastern United States indicate that while teachers see the value in teaching to think with models (i.e., during inquiry practices), they tend to use models mostly as communication tools in the classroom. Quantitative data collected about the modeling practices of 42 middle school students who worked collaboratively in small groups (4-5 students) using a computer modeling program indicated that students tended to engage in more mechanistic and function-related thinking with time as they reasoned about a complex system. Further, students had a typified trajectory of first adding and then next paring down ideas in their models. Implications for science education are discussed.